Chlorhexidine Prevents Root Dentine Mineral Loss and Fracture Caused by Calcium Hydroxide over Time - Michael Ranniery Garcia Ribeiro; Érika Bárbara Abreu Fonseca Thomaz; Darlon Martins Lima; Tarcísio Jorge Leitão; José Bauer; Soraia De Fátima Carvalho Souza (International Journal of Dentistry)
Purpose. To evaluate the mineral ion loss of root dentine after treatment with 2% chlorhexidine solution (CHX) and to compare its yield and flexural strength (fs) after exposure to calcium hydroxide [Ca(OH)2]. Materials and Methods. Dentine bars (DB) were made from 90 roots of bovine incisors and randomized into three groups: GControl: distilled/deionized water (DDW), GNaOCl: 2.5% sodium hypochlorite + 17% EDTA, and GCHX: CHX + DDW. The release of phosphate (PO4) and calcium (Ca) ions was measured by spectrophotometry. The DB were exposed to Ca(OH)2 paste for 0, 30, 90, and 180 days. DB were subjected to the three-point bending test to obtain yield and fs values. The fracture patterns were evaluated (20x). Data were analyzed using Kruskal-Wallis and Dunn’s post hoc tests or one- and two-way ANOVA followed by Tukey’s post hoc test (α=0.05). Results. GCHX showed lower PO43- and Ca2+ ionic release than GNaOCl (p<0.001). For yield and fs, GCHX>GNaOCl in all periods (p<0.001), except for yield strength values on 90 days (p=0.791). A larger frequency of vertical fractures was observed in GNaOCl and that of oblique fractures in GCHX (p<0.05). Conclusions. CHX prevented PO43- and Ca2+ loss and showed a tendency to preserve the yield and fs of root dentine over time following exposure to Ca(OH)2 paste.